A study of the motor response speed of the arms on the performance of some types of basketball scoring - Assistant Lecturer. Younis Sabih Abdullah (Zien Journals, 2023)
The game of basketball is a group game that has several basic principles, and its mastery depends on following proper planning. By informing the player of the performance of the basketball players, he noticed the appearance of signs of fatigue in the performance of the players as a result of the nervous tension and psychological pressure of the matches. He began to lose his focus in performing the skill of scoring, especially jumping. During the final times of the match, the researcher resorted to studying this situation among the players in order to develop appropriate solutions in order to avoid mistakes during the matches
Keywords: response; basketball; group games; Maysan Oil Club